2003
DOI: 10.1002/jcp.10314
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin sphingomyelin changes in cell proliferation and/or apoptosis induced by ciprofibrate

Abstract: It has been shown that neutral-sphingomyelinase and sphingomyelin-synthase activities are present in chromatin and they modify the sphingomyelin (SM) content. The activity of the first enzyme is stimulated and the second inhibited, when the hepatocytes enter into the S-phase after partial hepatectomy, thus suggesting that ceramide may have a pivotal role in cell proliferation. An opposite function was attributed to ceramide in hepatocytes which undergo apoptosis after lobular ligature. In order to clarify this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…Earlier reports have shown the existence of cholesterol in cell nucleus of regenerating liver cells [32,33] and a presence of highly expressed cholesterol transporter, PBR, in breast cancer cells [19,34]. Our study has also shown an increased expression of PBR in nuclear fraction of lymphocytes from CLL patients as compared to control subjects (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Earlier reports have shown the existence of cholesterol in cell nucleus of regenerating liver cells [32,33] and a presence of highly expressed cholesterol transporter, PBR, in breast cancer cells [19,34]. Our study has also shown an increased expression of PBR in nuclear fraction of lymphocytes from CLL patients as compared to control subjects (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…In fact, during proliferation, chromatin SMS decreases whereas the one localized in the nuclear envelope increases, while an opposite profile has been observed during apoptosis. 90,91 The changes in chromatin-associated SMS might regulate accessibility of DNA for transcription by regulation of DNA associated SM, similarly to what observed in the case of double stranded RNA. 92 Surprisingly, neither SMS1 nor SMS2 localize to the nucleus and so the identities of the nuclear SMS activities remain to be established.…”
Section: Resultsmentioning
confidence: 60%
“…The presence of this enzyme was demonstrated both in the nuclear membrane and in the isolated chromatin (Albi et al 2003a). The activity found in the whole homogenate was 0.93 pmol/mg protein/min, in the cytosol 2.61 pmol/mg protein/min and in the nuclear membrane 0.87 pmol/mg protein/min.…”
Section: Reverse Sphingomyelin-synthasementioning
confidence: 98%
“…No specific variations in the amounts of PI have been described during liver regeneration although it may have a role through its degradation enzymes by producing DAG (Albi et al 2003a). …”
Section: Pi Behaviourmentioning
confidence: 99%